Pembaharuan Sistem Hukum Nasional Terkait Pengesahan Perjanjian Internasional dalam Perlindungan Hak Konstitusional - Erlina Maria Christin Sinaga; Grenata Petra Claudia (The Constitutional Court of the Republic of Indonesia, 2021)
In making international agreements, the political influence of the presidential authority dominates over the authority the House of Representative. Ideally, the President and the DPR should be able to provide cumulative interpretations for the primat national law and international law on an international treaty. In the judicial review case, the Constitutional Court stated that Article 10 of the International Treaty Law was declared conditionally unconstitutional as long as only certain types of international agreements had to be approved by the DPR with a law. This paper wants to discuss the implications of the Constitutional Courts decision and the mechanism for making and ratification of International Agreement. The research method used is juridical normative with regulation and decision approaches. The result of study show thatapproval from DPR is a form of representation of the people which is a manifestation of the implementation of the principle of democracy. The Proposed Amendment to Law Number 24 of 2000 concerning International Treaties has been included in the National Legislation Program with the aim of perfecting the Law on International Treaties and harmonizing it with other laws and Contitutional Court’s decisions. So, the proposed Amendment, the mechanism for making and ratifying international agreements will increasingly prioritize National Interests and not harm the regions.